EXPLORING THE POTENTIAL OF SOIL STABILIZED MUD BLOCKS ENRICHED WITH COMBINED CONSTRUCTION AND DEMOLITION WASTE: AN INTRIGUING INVESTIGATION - Niyaz Ahmad Dar (Bulletin of Engineering Science, Technology and Industry, 2024)
This study investigates the utilization of construction and demolition (C&D) waste, particularly brick and concrete waste, in soil stabilization techniques for the production of sustainable building materials. Traditional civilizations laid the groundwork for soil stabilization methods, but the scientific understanding of these techniques emerged in the early 20th century. Compared to conventional construction materials, soil stabilized mud blocks offer advantages such as improved strength, durability, environmental sustainability, and cost-effectiveness. With the pressing global issue of managing C&D waste, this research explores the potential of incorporating such waste materials into soil samples sourced from nearby demolition sites. The experimental investigation involves creating cylindrical samples with varying ratios of C&D waste and soil, supplemented with different cement contents. Tests on compressive strength and water absorption properties are conducted to assess the suitability of the stabilized samples for construction applications. Additionally, the study extends to the production of concrete and stabilized mud blocks using cylindrical samples containing different proportions of C&D waste. Mechanical and physical properties of these blocks are analyzed to evaluate their performance and potential as sustainable building materials.